2011
DOI: 10.1002/ijc.26184
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lignan and proanthocyanidin consumption and colorectal adenoma recurrence in the Polyp Prevention Trial

Abstract: Lignans and proanthocyanidins are plant polyphenols that have shown protective properties against colorectal neoplasms in some human studies. Using logistic regression, we estimated odds ratios (ORs) and 95% confidence intervals (CIs) to prospectively evaluate the association between lignan and proanthocyanidin intake, estimated from databases linked to a food frequency questionnaire, and adenoma recurrence in 1,859 participants of the Polyp Prevention Trial. Overall, individual or total lignans or proanthocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In this study, PACs were mainly brought by fruits, wine, and legumes and similar to the Italian study, the protective effect of PACs was more pronounced for rectal than for colon cancer (223). In opposition with these studies, another Scottish case–control study and the prospective Iowa Women’s Health Study did not detect any association between PAC intake and colorectal cancer (224, 225) and Bobe et al, in 1,859 participants of the Polyp Prevention Trial, reported an association between PAC intake and the risk of colorectal adenoma recurrence in men (226). …”
Section: The Pacs In the Colonmentioning
confidence: 96%
“…In this study, PACs were mainly brought by fruits, wine, and legumes and similar to the Italian study, the protective effect of PACs was more pronounced for rectal than for colon cancer (223). In opposition with these studies, another Scottish case–control study and the prospective Iowa Women’s Health Study did not detect any association between PAC intake and colorectal cancer (224, 225) and Bobe et al, in 1,859 participants of the Polyp Prevention Trial, reported an association between PAC intake and the risk of colorectal adenoma recurrence in men (226). …”
Section: The Pacs In the Colonmentioning
confidence: 96%
“…However, ENL concentration in plasma or urine was not associated with risk of developing breast cancer in the European Prospective Investigation into Cancer and Nutrition—Norfolk cohort, suggesting that it is disease status that affects ENL production rather than ENL concentrations that affect breast cancer development. Associations between plasma ENL concentrations and other disease states have been proposed, including lower risk of colorectal adenoma . In combination with specific genetic risk alleles for gastric cancer, enterolactone and other phytoestrogens showed interaction with gastric cancer risk.…”
Section: Factors Affecting Variation In Plasma Enterolactonementioning
confidence: 99%
“…A recent analysis of lignan intake and adenoma recurrence in the Polyp Prevention Trial found a positive association in women (OR 5 2.07, 95% CI 1.22À3.52) but not in men. 41 It is likely that these inconsistent results reflect the diverse sources of lignans in the diet, in addition to the difficulty of accurately estimating dietary lignan intake. A recent study estimated total intake of lignans from food consumption data for adult men and women (19À79 years) from Denmark, Finland, Italy, Sweden, United Kingdom.…”
Section: Biological Activity and Anticancer Properties Of Whole-grainmentioning
confidence: 42%